Humidifying member and humidifying member with packaging material

By attaching a dispersion of small particles on the surface of the damp-regulating body, the liquid is adsorbed to prevent the adhesion and aggregation of the damp-regulating body, the problem of insufficient maintenance ability of the damp-regulating material under the target humidity is solved, and a moisture-regulating component with high fluidity and water retention is achieved.

CN120187512APending Publication Date: 2025-06-20SHARP KK
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380079145.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-11-17
Filing Date
2023-11-07
Publication Date
2025-06-20

AI Technical Summary

Technical Problem

The existing moisture-regulating materials have a large water change rate under specific humidity, resulting in insufficient maintenance ability under the target humidity, and it is difficult to simultaneously improve fluidity and inhibit liquid leakage.

Method used

By attaching a dispersion with a smaller average particle size than the average particle size of the damp-regulating body on the surface of the damp-regulating body, the dispersion adsorbs the liquid in the damp-regulating body, thereby preventing adhesion and aggregation between the damp-regulating bodies and improving water retention to inhibit liquid leakage.

Benefits of technology

The humidity-regulating components with high fluidity and low ooze at the target humidity are achieved, which simplifies the filling and processing of packaging materials and avoids the problems of liquid leakage and liquid leakage of packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120187512A_ABST
    Figure CN120187512A_ABST
Patent Text Reader

Abstract

Problems caused by a liquid present on the surface of a humidity control body are solved. The humidity control member includes: a plurality of humidity control bodies having a surface and containing a liquid that absorbs or releases moisture; and a plurality of dispersions having an average particle diameter smaller than the average particle diameter of the plurality of humidity control bodies, the plurality of dispersions adhering to the surface, adsorbing a portion of the liquid from the surface, and dispersing the plurality of humidity control bodies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a humidity conditioning member and a humidity conditioning member with a packaging material. This application claims the priority of Japanese Patent Application No. 2022-183764 filed in Japan on November 17, 2022, and incorporates its content herein by reference. Background Art

[0002] Patent Document 1 discloses an anti-caking agent. The anti-caking agent is composed of silica gel fine powder with an average particle size of 5 to 100 nm. The anti-caking agent is added to powdery or granular aromatic compounds. Thereby, caking of powdery or granular aromatic compounds can be prevented (paragraphs 0005 and 0006). Prior Art Documents Patent Documents

[0003] Patent Document 1: Japanese Unexamined Patent Application Publication No. 2000-87005 Summary of the Invention Technical Problem to be Solved by the Invention

[0004] A humidity conditioning material that absorbs moisture by dissolving water vapor in the atmosphere into the humidity conditioning material or releases moisture from the humidity conditioning material by volatilizing water vapor into the atmosphere to adjust the humidity of the surrounding air has an excellent maintaining ability at the target humidity due to its large moisture change rate at a specific humidity, and has a larger moisture absorption amount and moisture release amount compared to a humidity conditioning material that stores water vapor in pores by physical adsorption or chemical adsorption. Such a humidity conditioning material generally contains a liquid composed of a humidity conditioning component and moisture. When the amount of water contained in the humidity conditioning material is small (when adjusting the humidity of the surrounding air to a low humidity), its surface exhibits strong adhesiveness, resulting in adhesion between the humidity conditioning materials or between the humidity conditioning material and surrounding objects, causing the humidity conditioning material to lose fluidity. This makes secondary processing such as filling and processing of the packaging material difficult. On the other hand, when the humidity conditioning material absorbs a large amount of moisture, or when the amount of moisture contained in the humidity conditioning material is large in order to adjust the humidity of the surrounding air to a high humidity, the surface of the humidity conditioning material contains a large amount of water and has weak adhesiveness due to the flow of water. Therefore, it is easy to perform the above-mentioned secondary processing on the humidity conditioning material. However, there is a possibility that the liquid leaks out from the humidity conditioning material, and there is also a possibility that the liquid leaks out from the packaging material packaging the humidity conditioning material to the outside. The anti-caking agent disclosed in Patent Document 1 can improve the fluidity of powdery or particulate aromatic compounds by preventing caking. However, for a humidity conditioning material containing a liquid composed of a humidity conditioning component and moisture, it is difficult for this anti-caking agent to simultaneously solve the problems of improving fluidity and suppressing liquid leakage.

[0005] The present invention has been made in view of this problem. An object of one aspect of the present disclosure is to provide a humidity control member and a humidity control member with a packaging material that have high fluidity and do not exude liquid, for example, by eliminating problems caused by liquid present on the surface of the humidity control body. Technical solutions for solving technical problems

[0006] The humidity control member according to the first aspect of the present disclosure includes: a plurality of humidity control bodies having a surface and containing a liquid that absorbs or releases moisture; and a plurality of dispersoids having an average particle size smaller than the average particle size of the plurality of humidity control bodies, the plurality of dispersoids being attached to the surface and adsorbing a part of the liquid from the surface.

[0007] The humidity control material with a packaging material according to the second aspect of the present disclosure includes: the humidity control material according to one aspect of the present disclosure; and a packaging material that packages the humidity control material and has air permeability. Description of the drawings

[0008] Figure 1 It is a cross-sectional view schematically showing the humidity control member of the first embodiment. Figure 2 It is a cross-sectional view schematically showing the humidity control member of the first embodiment in the case where the dispersoid is composed of diatomaceous earth porous spheres. Figure 3 It is an image of a test product of the humidity control member of the first embodiment in the case where the humidity control body has a target humidity of 45% RH and the dispersoid is composed of diatomaceous earth porous spheres. Figure 4 It is an image of a test product of the humidity control member of the first embodiment in the case where the humidity control body has a target humidity of 90% RH and the dispersoid is composed of diatomaceous earth porous spheres. Figure 5 It is a cross-sectional view schematically showing the humidity control member of the first embodiment in the case where the dispersoid is composed of a silicate mineral. Figure 6 It is a perspective view schematically showing a state before swelling of montmorillonite, which is an example of the silicate mineral constituting the dispersoid included in the humidity control member of the first embodiment. Figure 7 It is a perspective view schematically showing a state after swelling of montmorillonite, which is an example of the silicate mineral constituting the dispersoid included in the humidity control member of the first embodiment. Figure 8 It is a cross-sectional view schematically showing the humidity control body included in the humidity control member of the first embodiment. Figure 9 It is a graph showing an example of a moisture sorption isotherm of a humidity control body including a water absorbent containing sodium polyacrylate and a humidity control component containing glycerol. Figure 10It is an image illustrating an evaluation method for the adhesiveness of Specimens 1-6. Figure 11 It is an image illustrating an evaluation method for the adhesiveness of Specimens 1-6. Figure 12 It is an image illustrating an evaluation method for the dispersibility of Specimens 1-6. Figure 13 It is an image illustrating an evaluation method for the dispersibility of Specimens 1-6. Figure 14 It is an image illustrating an evaluation method for whether liquid oozes out from Specimens 1-5. Figure 15 It is an image illustrating an evaluation method for whether liquid oozes out from Specimens 1-5. Figure 16 It is a graph showing the increase in the weight of the blotting paper before a specimen bag containing Specimens 1-5 is left standing on the blotting paper. Figure 17 It is a graph showing the moisture conditioning speed of Specimens 1-4. Figure 18 It is a diagram illustrating the composition of the moisture conditioning member of the second embodiment. Figure 19 It is a cross-sectional view schematically showing the moisture conditioning member with a packaging material of the first example of the third embodiment. Figure 20 It is a cross-sectional view schematically showing the moisture conditioning member with a packaging material of the second example of the third embodiment. Figure 21 It is a cross-sectional view schematically showing the moisture conditioning member with a packaging material of the fourth embodiment. Figure 22 It is a diagram showing the color change of the indication label provided in the moisture conditioning member with a packaging material of the fourth embodiment. Figure 23 It is an image of a prototype of the moisture conditioning member of the first reference example. Figure 24 It is a cross-sectional view schematically showing the moisture conditioning member with a packaging material including the moisture conditioning member of the first reference example. Figure 25 It is an image of a prototype of the moisture conditioning member of the second reference example. Figure 26 It is a cross-sectional view schematically showing the moisture conditioning member with a packaging material including the moisture conditioning member of the second reference example. Detailed Embodiments

[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. In addition, for the drawings, the same or equivalent elements are denoted by the same reference numerals, and repeated explanations are omitted.

[0010] 1 First Reference Example Figure 23 It is an image of a prototype of the humidity control component of the first reference example. Figure 24 It is a cross-sectional view schematically showing the humidity control component with the humidity control component of the first reference example and the packaging material.

[0011] As Figure 23 and Figure 24 shown, the humidity control component 901 of the first reference example includes a plurality of humidity control beads 911. As Figure 24 shown, the humidity control component 921 with the humidity control component 901 of the first reference example and the packaging material includes a packaging material 931.

[0012] The humidity control beads 911 contain a liquid composed of a humidity control component and moisture. The humidity control beads 911 have the function of adjusting the relative humidity of the surrounding air to the equilibrium humidity of the humidity control beads 911. Therefore, this equilibrium humidity becomes the target humidity of the humidity control beads 911. When the relative humidity of the air around the humidity control beads 911 is higher than the target humidity of the humidity control beads 911, it absorbs moisture from the surrounding air. When the relative humidity of the air around the humidity control beads 911 is lower than the target humidity of the humidity control beads 911, it releases moisture to the air around the humidity control beads 911. The humidity control beads 911 have a low target humidity of about 40% RH. The packaging material 931 packages the humidity control beads 911. The packaging material 931 has a bag-like shape. The packaging material 931 is composed of a non-woven fabric or a moisture-permeable film.

[0013] There is also a liquid composed of a humidity control component and moisture on the surface of the humidity control beads 911. When the humidity control beads 11 have a low target humidity of about 40% RH, the amount of moisture present on the surface of the humidity control beads 911 is small. Therefore, the liquid present on the surface of the humidity control beads 911 contains the humidity control component at a high concentration and has high viscosity. Therefore, the humidity control beads 911 adhere to each other or to surrounding objects strongly. Therefore, the humidity control beads 911 aggregate and only have low fluidity. Therefore, when actually using a plurality of humidity control beads 911 as a humidity control material, it is difficult to use a plurality of automatic filling and packaging devices, etc. to package and process the plurality of humidity control beads 911 into a breathable packaging material, etc. for secondary processing. The humidity control beads 911 contain a liquid composed of a humidity control component and moisture.

[0014] 2 Second reference example Figure 25 It is an image of a prototype of the humidity control component of the second reference example. Figure 26 It is a cross-sectional view schematically showing the humidity control component with the humidity control component of the second reference example and the packaging material.

[0015] As Figure 25 and Figure 26 shown, the humidity control component 951 in the second reference example includes a plurality of humidity control beads 961. As Figure 26The humidity control member 971 with the packaging material, which has the second reference example, includes the packaging material 981.

[0016] The humidity control beads 961 contain a liquid composed of a humidity control component and more moisture. When the relative humidity of the air around the humidity control beads 961 is higher than the target humidity of the humidity control beads 961, moisture is absorbed from the surrounding air. When the relative humidity of the air around the humidity control beads 961 is lower than the target humidity of the humidity control beads 961, moisture is released to the air around the humidity control beads 911. The humidity control beads 961 have a high target humidity of about 90% RH. The packaging material 981 packages the humidity control beads 961. The packaging material 981 has a bag-like shape. The packaging material 981 is composed of a non-woven fabric or a moisture-permeable film.

[0017] On the surface of the humidity control beads 961, there is also a liquid 962 composed of a humidity control component and more moisture. When the humidity control beads 961 have a high target humidity of about 90% RH, the amount of moisture present on the surface of the humidity control beads 911 is large. Therefore, the liquid 962 present on the surface of the humidity control beads 961 contains the humidity control component at a low concentration and has low viscosity. Therefore, the humidity control beads 911 only adhere to each other or weakly to surrounding objects. Therefore, the humidity control beads 911 do not aggregate and have high fluidity. Therefore, it is easy to package and process the humidity control beads 911 into secondary processed products such as breathable packaging materials using an automatic filling and packaging device, etc. However, the liquid 962 seeps out from the humidity control beads 961. Therefore, the liquid 962 leaks out from the packaging material 981. The leaked liquid 962 may adhere to storage objects, etc., stored together with the humidity control member 921 with the packaging material.

[0018] 3 First Embodiment 3.1 Humidity Control Member Figure 1 It schematically shows a cross-sectional view of the humidity control member of the first embodiment.

[0019] Figure 1 The shown humidity control member 1 of the first embodiment is different from the humidity control member 901 of the first reference example and the humidity control member 951 of the second reference example. It does not aggregate and does not allow the liquid to seep out.

[0020] As Figure 1 shown, the humidity control member 1 includes a plurality of humidity control bodies 11 and a plurality of dispersants 12. The humidity control bodies 11 are also referred to as humidity control materials, etc. The dispersants 12 are also referred to as dispersing materials, etc.

[0021] 3.2 Humidity Control Body The humidity control body 11 has a powdery, granular or particulate shape. The humidity control body 11 preferably has an average particle size of 0.1 mm or more and 10 mm or less. The average particle size referred to here is the average value of the equivalent spherical diameters. The humidity control body 11 is, for example, a humidity control bead having a spherical shape and a diameter of 3 mm or more and 6 mm or less.

[0022] The humidity control body 11 has water absorption. Therefore, the humidity control body 11 can contain moisture.

[0023] The humidity control body 11 absorbs or releases moisture. Therefore, the humidity control body 11 has humidity control ability. Therefore, when the relative humidity of the air around the humidity control body 11 is higher than the target humidity of the humidity control material 1, moisture is absorbed from the air around the humidity control body 11, and when the relative humidity of the air around the humidity control material 1 is lower than the target humidity of the humidity control material 1, moisture is released to the air around the humidity control body 11. Compared with a desiccant represented by type A silica gel, the humidity control body 11 can desorb water by heating at a lower temperature. In addition, the humidity control body 11 can repeatedly absorb or release moisture. Therefore, in principle, the humidity control body 11 can maintain the humidity control ability semi-permanently. The target humidity of the humidity control body 11 can be adjusted by the material constituting the humidity control body 11.

[0024] 3.3 Dispersion The dispersion 12 has a particulate shape. The dispersion 12 has an average particle size smaller than the average particle size of the humidity control body 11, and preferably has an average particle size of 1 μm or more and 100 μm or less. The average particle size referred to here can be measured by, for example, the median diameter D50 measured by the laser diffraction / scattering method.

[0025] The dispersion 12 adheres to the surface of the humidity control body 11. Thereby, the dispersion 12 adsorbs a part of the liquid contained in the humidity control body 11 from the surface of the humidity control body 11. Here, adsorbing a part of the liquid means that by adsorbing the liquid and enclosing it inside the dispersion or between pores and crystal layers, a slightly residual surface property of the dispersion itself remains, and at least the state where the surface of the dispersion is not covered by the liquid is formed. The adsorbed liquid contains a humidity control component and moisture. The higher the concentration of the humidity control component, the higher the viscosity of the liquid.

[0026] Since even after adsorbing the liquid, only a small amount of the original surface property of the dispersion 12 remains, they do not stick or adhere to each other. Therefore, the dispersion 12 remains dispersed after adsorbing the liquid and does not aggregate.

[0027] Thereby, the dispersion 12 hinders the humidity control bodies 11 from sticking to each other. Thereby, the dispersion 12 disperses the humidity control bodies 11 and suppresses the aggregation of the humidity control bodies 11.

[0028] In addition, the dispersion 12 improves the water retention or liquid retention property of the humidity control member 1. Thereby, the leakage of the liquid from the humidity control member 1 can be suppressed. Thereby, when the humidity control member 1 is packaged with a packaging material, the leakage of the liquid from the packaging material can be suppressed.

[0029] The dispersion 12 is chemically stable with respect to the humidity control component contained in the humidity control body 11. The dispersion 12 has high safety.

[0030] The dispersion 12 contains at least one selected from the group consisting of silicate compounds such as porous silica gel, zeolite, silica powder, diatomaceous earth (volcanic ash), silicate minerals (clay minerals), activated clay, and acid clay, preferably contains at least one selected from the group consisting of silica-containing materials such as silica powder and diatomaceous earth and silicate minerals, and more preferably contains at least one selected from the group consisting of diatomaceous earth and silicate minerals. The diatomaceous earth may be diatomaceous earth porous spheres.

[0031] The main component of diatomaceous earth is silicic acid (silica).

[0032] The diatomaceous earth porous spheres are obtained by heat-treating diatomaceous earth to cause foaming and have a hollow structure. The diatomaceous earth porous spheres are mainly composed of hollow silica.

[0033] The addition amount of the dispersion 12 with respect to the humidity control body 11 is sufficient even in a small amount.

[0034] The humidity control member 1 can be manufactured by mixing the humidity control body 11 and the dispersion 12 with each other using a mixer or the like.

[0035] 3.4 Case where the dispersion is composed of diatomaceous earth porous spheres Figure 2 It is a cross-sectional view schematically showing the humidity control member of the first embodiment in the case where the dispersion is composed of diatomaceous earth porous spheres.

[0036] As Figure 2 shown, when the dispersion 12 is composed of diatomaceous earth porous spheres, each dispersion 12 has a hollow structure. Therefore, pores 12a are formed inside each of the dispersions 12. Thereby, each of the dispersions 12 can suck the liquid 21 adsorbed from the surface of the humidity control body 11 into the inside of the pores 12a. Even after the liquid 21 is sucked into the inside of the pores 12a and surrounds the pores 12a, the outer shell 31 made of silica also retains its original surface properties and thus does not aggregate.

[0037] Figure 3 It is an image of a test product of the humidity control member of the first embodiment in the case where the humidity control body has a target humidity of 45% RH and the dispersion is composed of diatomaceous earth porous spheres. Figure 4This is an image of a prototype of a humidity control component according to a first embodiment where the humidity control body has a target humidity of 90% RH and the dispersion is composed of diatomaceous earth porous spheres.

[0038] As Figure 3 and Figure 4 shown, when the humidity control body 11 has either a target humidity of 45% RH or 90% RH, and the dispersion 12 is composed of diatomaceous earth porous spheres, the humidity control components 1 do not stick to each other but roll as individual particles. This means that the diatomaceous earth porous spheres can inhibit the aggregation of the humidity control components 1.

[0039] 3.5 Case where the dispersion is composed of silicate minerals Figure 5 This is a cross-sectional view schematically showing a humidity control component according to a first embodiment where the dispersion is composed of silicate minerals.

[0040] As Figure 5 illustrated, when the dispersion 12 is composed of silicate minerals, the silicate crystal layers constituting the dispersion 12 have a negative surface charge and can adsorb a liquid containing moisture between their layers. Thus, each dispersion 12 can absorb the liquid 21 adsorbed from the surface of the humidity control body 11 between the silicate crystal layers. Even after the liquid 21 is absorbed between the silicate crystal layers, the silicate crystal layers maintain a negative surface charge and retain their original surface properties, thus repelling each other. Therefore, the dispersions 12 do not aggregate.

[0041] Figure 6 This is a perspective view schematically showing the state before swelling of smectite, which is an example of the silicate minerals constituting the dispersion of the humidity control component according to the first embodiment. Figure 7 This is a perspective view schematically showing the state after swelling of smectite, which is an example of the silicate minerals constituting the dispersion of the humidity control component according to the first embodiment.

[0042] Figure 6 and Figure 7 shown, the smectite 41 contains silicate crystal layers 51, potassium ions 52, sodium ions 53, calcium ions 54, magnesium ions 55, and water molecules 56.

[0043] The silicate crystal layers 51 are negatively charged.

[0044] The silicate crystal layers 51 are stacked. Potassium ions 52, sodium ions 53, calcium ions 54, magnesium ions 55, and water molecules 56 exist between two adjacent silicate crystal layers 51. The water molecules 56 can insert and escape between the layers.

[0045] Therefore, when the dispersion 12 is composed of smectite 41, the dispersion 12 has the liquid absorption property of the liquid from the surface of the humidity control body 11.

[0046] In addition, when the dispersion 12 is composed of smectite 41, the dispersions 12 repel each other due to the surface charges generated by the negatively charged silicate crystal layers 51. Therefore, the dispersions 12 do not aggregate.

[0047] 3.6 Materials constituting the humidity control body Figure 8 is a cross-sectional view schematically showing the humidity control body included in the humidity control member of the first embodiment.

[0048] As Figure 8 shown, the humidity control body 11 includes a water absorbent body 71 and a humidity control component 72, respectively. The water absorbent body 71 is composed of a water absorbent material 81. The water absorbent body 71 may contain elements other than the water absorbent material 81. The humidity control component 72 is present in the water absorbent material 81. The humidity control component 72 absorbs or releases moisture. The humidity control component 72 includes a deliquescent component. The humidity control body 11 is manufactured by infiltrating a liquid containing the humidity control component 72 into the water absorbent body 71.

[0049] The water absorbent material 81 contains, for example, at least one selected from the group consisting of a water-absorbing resin and a clay mineral.

[0050] The water-absorbing resin may be an ionic resin or a non-ionic resin. The water-absorbing resin has a granular or particulate shape.

[0051] The ionic resin includes, for example, at least one selected from the group consisting of an alkali metal salt of polyacrylic acid and a starch-acrylate graft polymer. The alkali metal salt of polyacrylic acid includes, for example, sodium polyacrylate.

[0052] The non-ionic resin includes, for example, at least one selected from the group consisting of a vinyl acetate copolymer, a maleic anhydride copolymer, polyvinyl alcohol, and a polyalkylene oxide.

[0053] The clay mineral contains at least one selected from the group consisting of, for example, a silicate mineral and a zeolite. The silicate mineral includes, for example, at least one selected from sepiolite, wollastonite, kaolin perlite, and dolomite.

[0054] The humidity control component 72 includes, for example, at least one selected from the group consisting of a polyol and a salt.

[0055] The polyol includes, for example, at least one selected from the group consisting of glycerol, propylene glycol, butylene glycol, pentylene glycol, trimethylolpropane, butanetriol, ethylene glycol, diethylene glycol, triethylene glycol, and lactic acid, and preferably includes a polyol having three or more hydroxyl groups. The polyol having three or more hydroxyl groups includes, for example, glycerol. The polyol may form a dimer or a polymer.

[0056] The salt preferably includes a metal salt, more preferably includes a deliquescent metal salt, such as includes at least one selected from the group consisting of carboxylate salts, carbonate salts, lithium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, aluminum chloride, zinc chloride, lithium bromide, potassium bromide, calcium bromide, and sodium hydroxide, and preferably includes at least one selected from the group consisting of carboxylate salts and carbonate salts.

[0057] The carboxylate salt includes, for example, at least one selected from the group consisting of sodium formate, potassium formate, sodium acetate, potassium acetate, lithium acetate, sodium propionate, potassium propionate, sodium lactate, potassium lactate, and sodium pyrrolidone carboxylate, and preferably includes at least one selected from the group consisting of sodium formate, sodium acetate, sodium propionate, and sodium lactate.

[0058] The carbonate salt includes, for example, at least one selected from the group consisting of sodium carbonate, potassium carbonate, and calcium carbonate.

[0059] The deliquescent metal salt preferably contains at least one selected from sodium formate, sodium acetate, sodium propionate, sodium lactate, sodium carbonate, and potassium carbonate, which have high safety and high hygroscopicity.

[0060] Each of the humidity control bodies 11 may contain at least one selected from the group consisting of a water-containing polymer material, a silicate compound material, and diatomaceous earth.

[0061] 3.7 Amount of water contained in the humidity control body Figure 9 It is a graph showing an example of the moisture sorption isotherm of a humidity control body having a water absorbent body composed of sodium polyacrylate and a humidity control component composed of an aqueous glycerol solution.

[0062] In Figure 9 In the shown graph, the horizontal axis is the relative humidity of the air around the humidity control body 11. In addition, the vertical axis represents the moisture content rate of the humidity control body 11, and the moisture content rate of the humidity control body 11 is the ratio of water to the humidity control component 72.

[0063] According to Figure 9 It can be understood that the higher the target humidity of the humidity control body 11, the greater the moisture content rate of the humidity control body 11. For example, when the target humidity of the humidity control body 11 is 50% RH, the moisture content rate of the humidity control body 11 is 25%, and when the target humidity of the humidity control body 11 is 90% RH, the moisture content rate of the humidity control body 11 is 146%.

[0064] Therefore, when the target humidity of the humidity conditioning body 11 is a low target humidity such as 50% RH, the moisture content rate of the humidity conditioning body 11 is a low moisture content rate such as 25%. As a result, the concentration of the humidity conditioning component 72 in the humidity conditioning component 72 and the liquid containing moisture becomes high. As a result, the viscosity of the liquid becomes high. Therefore, the humidity conditioning body 11 may aggregate. When the target humidity of the humidity conditioning body 11 is low, the dispersion 12 retains the surface properties of the dispersion 12 by adsorbing a part of the liquid from the surface of the humidity conditioning body 11, and thus reduces the adhesiveness of the humidity conditioning member 1. The dispersion 12 becomes a spacer between the humidity conditioning bodies 11 and inhibits the aggregation of the humidity conditioning member 1.

[0065] On the other hand, when the target humidity of the humidity conditioning body 11 is a high target humidity such as 90% RH, the moisture content rate of the humidity conditioning body 11 is a high moisture content rate such as 146%. As a result, the concentration of the humidity conditioning component 72 in the humidity conditioning component 72 and the liquid containing moisture decreases. As a result, the viscosity of the liquid becomes low. Therefore, the humidity conditioning body 11 does not aggregate and has fluidity. However, there is a possibility that the liquid may ooze out from the humidity conditioning body 11. When the target humidity of the humidity conditioning body 11 is high, the dispersion 12 improves the water retention or liquid retention of the humidity conditioning member 1 by absorbing the liquid from the surface of the humidity conditioning body 11. Thereby, the dispersion 12 inhibits the liquid from oozing out from the humidity conditioning member 1.

[0066] 3.8 Changes in the adhesiveness and dispersibility of the humidity conditioning member due to the type of dispersion A humidity conditioning body 11 was prepared, which has a water absorbent body made of sodium polyacrylate and a humidity conditioning component made of glycerin and water, and has a target humidity of 50% RH.

[0067] A specimen 1 composed of the produced humidity conditioning body 11 was prepared. In addition, the dispersions shown in Table 1 were added to the produced humidity conditioning body 11 to prepare specimens 2 - 6. Table 1 shows the material, average particle size, addition rate, and presence or absence of water absorbency of the dispersions.

[0068] [Table 1]

[0069] The adhesiveness and dispersibility of the prepared specimens 1 - 6 were evaluated.

[0070] Figure 10 and Figure 11 are images illustrating the evaluation method of the adhesiveness of specimens 1 - 6.

[0071] In the evaluation of the adhesiveness of the specimen, a specimen having a weight of 50 g was placed in a plastic container having a cylindrical outer shape with an internal volume of 300 ml. Then, as Figure 10 shown, the plastic container was placed on the surface such that the axial direction of the plastic container pointed in the vertical direction. Then, as Figure 11As shown, turn the plastic container upside down. Then, measure the dropping time required for the entire sample to fall. Table 1 shows the measured dropping times. A long measured dropping time indicates high adhesiveness of the sample.

[0072] Figure 12 and Figure 13 are images illustrating the evaluation method for the dispersibility of Samples 1 - 6.

[0073] In the evaluation of the dispersibility of the sample, place a sample with a weight of 50 g into a plastic container having a cylindrical outer shape with an inner volume of 300 ml. Then, place the plastic container on a surface such that the axial direction of the plastic container is horizontal. Then, as Figure 12 and Figure 13 shown, roll the plastic container in a circular direction on the surface. Then, measure the angle of repose at which the inclined plane formed by the stationary sample becomes horizontal. Table 1 shows the measured angles of repose. A small measured angle of repose means high dispersibility of the sample.

[0074] As shown in Table 1, the dropping time of Sample 1 without the addition of the dispersant is longer than 60 seconds. The dropping times of Samples 2, 3, 4, 5, and 6 with the addition of diatomaceous earth porous spheres, silicate minerals, spherical polymethyl methacrylate resins, spherical polystyrene resins, and sodium polyacrylate, respectively, are shorter than 1 second. From this, it can be known that by adding diatomaceous earth porous spheres, silicate minerals, spherical polymethyl methacrylate resins, or spherical polystyrene resins to the humidity control body 11, the adhesiveness of the humidity control component can be reduced. Here, when sodium polyacrylate is added to the humidity control body 11, the dropping time is short, and a short dropping time means that the entire humidity control body 11 aggregates and falls, so it does not indicate a reduction in the adhesiveness of the humidity control component.

[0075] In addition, as shown in Table 1, the angle of repose of Sample 1 without the addition of the dispersant is 50°. The angles of repose of Samples 2 and 3 with the addition of diatomaceous earth porous spheres and silicate minerals, respectively, are 30°. The angles of repose of Samples 4 and 5 with the addition of spherical polymethyl methacrylate resins and spherical polystyrene resins, respectively, are 32°. The angle of repose of Sample 6 with the addition of sodium polyacrylate is greater than 50°. Considering these aspects, it can be understood that by adding diatomaceous earth porous spheres, silicate minerals, spherical polymethyl methacrylate resins, or spherical polystyrene resins to the humidity control body 11, the dispersibility of the humidity control component can be improved. In addition, it can be understood that by adding sodium polyacrylate to the humidity control body 11, the dispersibility of the humidity control component is reduced. This indicates that when sodium polyacrylate absorbs liquid from the surface of the humidity control body 11, since the liquid exists not only inside but also on the entire surface, sodium polyacrylate becomes a covered state, so the adhesiveness is not improved. That is, it can be known that regardless of the particle size and the presence or absence of water absorbency, the dispersant that adsorbs a part of the liquid from the surface of the humidity control body 11 is important for the adhesiveness dependence.

[0076] 3.9 Variation in liquid exudation from the humidity control component due to the type of dispersion A humidity control body 11 was prepared, which had a water-absorbing body composed of sodium polyacrylate and a humidity control component composed of glycerin, and had a target humidity of 90% RH.

[0077] A test specimen 1 composed of the produced humidity control body 11 was prepared. In addition, the dispersions shown in Table 2 were added to the produced humidity control body 11 to prepare test specimens 2-5. Table 2 shows the material, average particle size, addition rate, and presence or absence of water absorbency of the dispersions.

[0078] [Table 2]

[0079] Figure 14 and Figure 15 is a diagram illustrating an evaluation method for whether liquid exudes from test specimens 1-5. Figure 16 is a graph showing the increase in the weight of the blotting paper before the bagged test specimens containing test specimens 1-5 were left standing on the blotting paper. In Figure 16 , the horizontal axis represents the type of test specimen. In addition, the vertical axis is set to the increase in the weight of the blotting paper.

[0080] Evaluate whether liquid exudes from the prepared test specimens 1-5.

[0081] In the evaluation of whether liquid exudes from the test specimen, the test specimen was housed in a bag formed of non-woven fabric to produce a bagged test specimen, where the bag can be used as a packaging material having air permeability. The bag is the "ultra-thin tea bag" manufactured by Zenmi Co., Ltd. The bag is composed of polyester and polyethylene. Then, as Figure 14 shown, the bagged test specimen was left standing on the blotting paper placed on the inner bottom surface of the container, and the container was covered. After 6 hours had passed since the bagged test specimen was left standing on the blotting paper, as Figure 15 shown, the lid was removed from the container, and the bagged test specimen was removed from the blotting paper. Then, it was confirmed whether there were stains on the blotting paper formed by liquid exuding from the test specimen. Table 2 shows whether there were stains on the confirmed blotting paper. In addition, the increase in the weight of the blotting paper with respect to the weight of the blotting paper before the bagged test specimen was left standing on the blotting paper was measured. Figure 16 Represents the measured increase in the weight of the blotting paper. Figure 16 Also shown is the increase in weight caused by the moisture absorption of the blotting paper in the case where the bagged test specimen was not left standing on the blotting paper (no test specimen). The presence of stains on the blotting paper or a large increase in the weight of the blotting paper means that liquid has exuded from the test specimen. That is, when there are no stains on the blotting paper and the increase in the weight of the blotting paper is small, the dispersion contained in the test specimen is inhibited from exuding liquid from the test specimen.

[0082] As shown in Table 2, there are stains on the blotting paper of the bagged sample of Sample 1 without added dispersion. There are no stains on the blotting paper of the bagged samples of Samples 2 and 3. Diatomite porous spheres and silicate minerals are added to Samples 2 and 3 respectively. There are stains on the blotting paper of the bagged samples of Samples 4 and 5. Spherical polymethyl methacrylate resin and spherical polystyrene resin are added to Samples 4 and 5 respectively. In addition, as Figure 16 shown, the weight increase of the blotting paper of the bagged sample of Sample 1 without added dispersion is significantly greater than that of the blotting paper without the bagged sample. The weight increase of the blotting paper of the bagged sample is only slightly larger than that of the blotting paper without the bagged sample. The bagged sample has Samples 2 and 3 with diatomite porous spheres and silicate minerals added respectively. The weight increase of the blotting paper of the bagged sample of Samples 4 and 5 is significantly greater than that of the blotting paper without the bagged sample. Spherical polymethyl methacrylate resin and spherical polystyrene resin are added to Samples 4 and 5 respectively. From these contents, it can be understood that by adding diatomite porous spheres or silicate minerals to the humidity control body 11, the above-mentioned dispersion adsorbs the liquid from the humidity control component, thereby suppressing the leakage of the liquid and the leakage of the liquid from the packaging material.

[0083] 3.10 Change in the humidity control speed of the humidity control component due to the type of dispersion A humidity control body 11 was prepared, which has a water absorbent body made of sodium polyacrylate and a humidity control component made of glycerin, and has a target humidity of 50% RH.

[0084] Sample 1 composed of the prepared humidity control body 11 was prepared. In addition, the dispersions shown in Table 3 were added to the prepared humidity control body 11 to prepare Samples 2-4. Table 3 shows the material, average particle size, addition rate, and presence or absence of water absorbency of the dispersion.

[0085] [Table 3]

[0086] The moisture absorption rates of the prepared Samples 1-4 were evaluated.

[0087] Figure 17 is a graph showing the moisture absorption rates of Samples 1-4.

[0088] In Figure 17 , the horizontal axis represents the type of sample. In addition, the vertical axis is set as the moisture absorption rate of the sample.

[0089] In the evaluation of the moisture absorption rate of the specimen, the specimen is left standing in a thermo-hygrostat at 23°C and 70% RH for 30 minutes. Then, the increase in the weight of the specimen compared to the weight of the specimen before it was placed in the thermo-hygrostat is measured. In addition, the moisture absorption rate of the specimen is calculated based on the measured increase in the weight of the specimen. Figure 17 Represents the calculated moisture absorption rate of the specimen.

[0090] As Figure 17 shown, the moisture absorption rate of Specimen 2 to which diatomaceous earth porous spheres were added was 40% lower than that of Specimen 1 to which no dispersion was added. In addition, the moisture absorption rate of Specimen 3 to which a silicate mineral was added was 30% lower than that of Specimen 1 to which no dispersion was added. The moisture absorption rate of Specimen 4 to which spherical polymethyl methacrylate resin was added was 50% lower than that of Specimen 1 to which no dispersion was added. From this, it can be seen that the reduction in the moisture absorption rate of Specimens 2 and 3 to which diatomaceous earth porous spheres and silicate minerals were added was less than the reduction in the moisture absorption rate of Specimen 4 to which spherical polymethyl methacrylate resin was added. It is considered that the decrease in the moisture absorption rate of Specimens 2 and 3 is relatively small because diatomaceous earth porous spheres and silicate minerals themselves have liquid-absorbing properties and function as humidity control materials.

[0091] 3.11 Preferred types of dispersions Based on the results of the above evaluation, it can be understood that by adding diatomaceous earth porous spheres or silicate minerals to the humidity control body 11, the adhesiveness of the humidity control member can be reduced, and the dispersibility of the humidity control member can be improved. That is, it can be understood that the aggregation of the humidity control member can be suppressed. In addition, it can be understood that by adding diatomaceous earth porous spheres or silicate minerals to the humidity control body 11, the leakage of liquid from the humidity control member can be suppressed. In addition, it can be understood that even if diatomaceous earth porous spheres or silicate minerals are added to the humidity control body 11, the humidity control rate will not be significantly reduced. In summary, by adding diatomaceous earth porous spheres or silicate minerals to the humidity control body 11, in a humidity control material containing a liquid composed of a humidity control component and moisture, the reduction of the humidity control function can be suppressed to a small extent, and the problems of improving fluidity and liquid leakage from the humidity control material can be solved simultaneously.

[0092] 4 Second Embodiment Hereinafter, the differences between the second embodiment and the first embodiment will be described. Regarding aspects not described, in the second embodiment, the same configuration as that employed in the first embodiment is also adopted.

[0093] Figure 18 is a diagram for explaining the components of the humidity control member of the second embodiment.

[0094] The humidity control member 2 of the second embodiment includes a humidity control body 11 and a dispersion 12 in the same manner as the humidity control member 1 of the first embodiment. Further, the humidity control member 2 is different from the humidity control member 1 in that it includes a functional member 13.

[0095] The humidity control body 11, the dispersion 12, and the functional material 13 are mixed with each other. The functional material 13 imparts functions other than the humidity control function to the humidity control member 2.

[0096] The functional material 13 includes, for example, at least one selected from the group consisting of a rust preventive material 91, an antibacterial material 92, and a deodorant material 93.

[0097] The rust preventive material 91 imparts a rust preventive function to the humidity control member 2. By imparting the rust preventive function to the humidity control member 2, it is possible to suppress the generation of rust on the metal material in the vicinity of the humidity control member 2. Thus, a humidity control member 2 suitable for storing metal parts can be provided. The rust preventive material 91 includes, for example, at least one selected from the group consisting of amine carboxylates, molybdates, chromates, silicates, zinc, and organic silicates. The organic silicate includes, for example, at least one selected from a resin containing an organosilane and ethyl silicate.

[0098] The antibacterial material 92 imparts an antibacterial function to the humidity control member 2. By adding the antibacterial function to the humidity control member 2, it is possible to suppress the spoilage, mold, etc. of drugs, foods, etc. in the vicinity of the humidity control member 2. Thus, a humidity control member 2 suitable for storing drugs and maintaining the freshness of foods can be provided. The antibacterial material 92 includes, for example, at least one selected from the group consisting of organic antibacterial materials, inorganic antibacterial materials, and natural antibacterial materials. The inorganic antibacterial material releases, for example, at least one selected from the group consisting of silver ions and zinc ions. The natural antibacterial material contains natural ingredients. The natural ingredients contain at least one selected from the group consisting of extracts of organisms and chitosan.

[0099] The deodorant material 93 adds a deodorant function to the humidity control member 2. By adding the deodorant function to the humidity control member 2, it is possible to suppress the generation of odors in drugs, foods, etc. in the vicinity of the humidity control member 2. Thus, a humidity control member 2 suitable for storing drugs and maintaining the freshness of foods can be provided. The deodorant material 93 includes, for example, activated carbon powder.

[0100] 5 Third Embodiment Figure 19 is a cross-sectional view schematically showing a humidity control member with a packaging material according to the first example of the third embodiment. Figure 20 is a cross-sectional view schematically showing a humidity control member with a packaging material according to the second example of the third embodiment.

[0101] As Figure 19 and Figure 20As shown, the humidity control component 101 with packaging material includes a humidity control component 111 and a packaging material 112.

[0102] The humidity control component 111 is the humidity control component 1 of the first embodiment or the humidity control component 2 of the second embodiment.

[0103] The packaging material 112 wraps the humidity control component 111. The packaging material 112 has air permeability. Thus, it is possible to inhibit the direct contact between the humidity control component 111 and the object to be humidity-controlled, and the humidity control component 111 can humidify the object to be humidity-controlled.

[0104] In the first example of the third embodiment, the packaging material 112 has a breathable packaging material 121. The breathable packaging material 121 has flexibility and a sheet-like shape. The breathable packaging material 121 is bent in such a way that the first end 131 and the second end 132 of the breathable packaging material 121 overlap each other. The overlapping first end 131 and second end 132 are joined to each other. The joining is performed by welding such as heat sealing. Thus, the packaging material 112 is given a pouch-like shape. Thus, the packaging material 112 can accommodate the humidity control component 111.

[0105] In the second example of the third embodiment, the packaging material 112 has a breathable packaging material 121 and a plastic container 122. The plastic container 122 has a certain shape. An opening is formed in the plastic container 122. The breathable packaging material 121 closes the opening. Thus, the packaging material 112 can accommodate the humidity control component 111.

[0106] A part of the packaging material 112 may also have transparency. Thus, the state of the humidity control component 111 accommodated in the packaging material 112 can be confirmed from the outside of the packaging material 112.

[0107] Air holes are formed in the breathable packaging material 121. The size of the air holes is smaller than the size of the humidity control body 11. Thus, it is possible to inhibit the humidity control body 11 and the dispersion 12 attached to its surface from passing through the breathable packaging material 121. As long as the size of the air holes is smaller than the size of the humidity control body 11, the packaging material 112 may also have a mesh structure with millimeter-sized holes. Preferably, the size of the air holes is smaller than the size of the dispersion 12. Thus, it is possible to further inhibit the dispersion 12 from passing through the breathable packaging material 121.

[0108] In order to manufacture the humidity conditioning member 101 with a packaging material, it is necessary to perform secondary processing such as packaging processing that houses the humidity conditioning member 111 in the packaging material 112 using an automatic filling and packaging device or the like. On the other hand, the aggregation of the humidity conditioning member 111 is suppressed by the dispersion 12, and thus it is easy to perform secondary processing on the humidity conditioning member 111. Therefore, the humidity conditioning member 101 with a packaging material can be easily manufactured. The same can be said when secondary processing other than filling and packaging processing, such as stirring and mixing with other materials, is required to manufacture a product including the humidity conditioning member 111.

[0109] 6 Fourth Embodiment Hereinafter, the differences between the fourth embodiment and the third embodiment will be described. Regarding aspects not described, in the fourth embodiment, the same configuration as that employed in the third embodiment is also adopted.

[0110] Figure 21 is a cross-sectional view schematically showing the humidity conditioning member with a packaging material of the fourth embodiment. Figure 22 is a diagram showing the color change of the indication label included in the humidity conditioning member with a packaging material of the fourth embodiment.

[0111] As Figure 21 shown, the humidity conditioning member 141 with a packaging material of the fourth embodiment includes an indication label 151.

[0112] The indication label 151 is disposed on the breathable packaging material 121. The indication label 151 is disposed in a region that occupies a part of the surface of the breathable packaging material 121. The indication label 151 exhibits a color corresponding to the humidity. When the equilibrium humidity of the humidity conditioning member 111 deviates from near the target humidity of the humidity conditioning member 111, the indication label 151 changes color. Thereby, when the equilibrium humidity of the humidity conditioning member 111 deviates from near the target humidity of the humidity conditioning member 111, it is possible to prompt the user to replace the humidity conditioning member 111 with a new one, regenerate the humidity conditioning member 111, or the like.

[0113] The indication label 151 contains an indication material whose color changes according to the humidity. The indication material includes, for example, at least one selected from the group consisting of cobalt chloride, cobalt bromide, phthalocyanine pigments, and compounds obtained by polymerizing triphenylmethane pigments such as phthalocyanine pigments.

[0114] The present invention is not limited to the above embodiments, and can be replaced with a configuration substantially the same as the configuration shown in the above embodiments, a configuration that achieves the same effect, or a configuration that can achieve the same purpose.

Claims

1. A humidity conditioning component, characterized in that, Comprising: A plurality of humidity conditioning bodies, having a surface and containing a liquid that absorbs or releases moisture; A plurality of dispersoids, having an average particle size smaller than the average particle size of the plurality of humidity conditioning bodies, the plurality of dispersoids being attached to the surface, adsorbing a part of the liquid from the surface and dispersing the plurality of humidity conditioning bodies.

2. The humidity conditioning component according to claim 1, characterized in that, The plurality of humidity conditioning bodies have an average particle size of 0.1 mm or more and 10 mm or less, The plurality of dispersoids have an average particle size of 1 μm or more and 100 μm or less.

3. The humidity conditioning component according to claim 2, characterized in that, The plurality of dispersoids contain at least one selected from silica and silicate compounds.

4. The humidity conditioning component according to claim 3, characterized in that, The plurality of dispersoids contain at least one selected from diatomaceous earth and silicate compounds.

5. The humidity conditioning component according to claim 4, characterized in that, Pores are formed inside each of the plurality of dispersoids.

6. The humidity conditioning component according to any one of claims 1 to 5, characterized in that, Each of the plurality of humidity conditioning bodies includes: a water absorbent body containing a water absorbent material; and A humidity conditioning component built in the water absorbent material, absorbing or releasing moisture, The liquid is composed of the humidity conditioning component and moisture.

7. The humidity conditioning component according to claim 6, characterized in that, The humidity conditioning component contains at least one selected from polyhydric alcohols and salts.

8. The humidity conditioning component according to claim 7, characterized in that, The salt contains a metal salt.

9. The humidity conditioning component according to claim 8, characterized in that, The salt contains at least one selected from the group consisting of carboxylates and carbonates.

10. The humidity conditioning component according to claim 6, characterized in that, The water absorbent material contains at least one selected from the group consisting of water-absorbing resins and clay minerals.

11. The humidity conditioning component according to any one of claims 1 to 5, characterized in that, Comprising at least one selected from the group consisting of rust-preventive materials, antibacterial materials, and deodorant materials.

12. The humidity conditioning component according to any one of claims 1 to 3, characterized in that, Pores are formed inside each of the plurality of dispersoids.

13. A humidity conditioning component with packaging material, characterized in that, Including: the humidity conditioning component according to any one of claims 1 to 5; and a packaging material that packages the humidity conditioning material and has air permeability.

14. The humidity conditioning component with packaging material according to claim 13, characterized in that, Further including an indication label disposed on the packaging material and presenting a color corresponding to humidity.

Citation Information

Patent Citations

  • Prevention of solidification

    JP2000087005A

  • Eliminable composition for forming film

    JP2022183764A